2003
DOI: 10.1089/152308603770380034
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hypertrophic and Apoptotic Signaling Pathways by Reactive Oxygen Species in Cardiac Myocytes

Abstract: Increasing evidence suggests that oxidative and nitrosative stress play an important role in regulation of cardiac myocyte growth and survival. The cardiovascular system is continuously exposed to both reactive oxygen species (ROS) and nitrogen species (RNS), collectively termed reactive inflammatory species (RIS), and imbalances between the enzymes that regulate their bioavailability are associated with cardiac hypertrophy and the pathogenesis of cardiomyopathies, myocardial infarction and heart failure. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
143
0
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(164 citation statements)
references
References 84 publications
5
143
0
13
Order By: Relevance
“…Obesity-related oxidative stress, inflammation, and activation of the renin-angiotensin system can induce cardiac remodeling with increased cardiac myocyte and connective tissue matrix accumulation. [33][34][35] The causality of the observed association between childhood adiposity and adulthood LVM cannot be established by this observational study. Persistence of adiposity over time plays a role in this regard.…”
Section: Discussionmentioning
confidence: 77%
“…Obesity-related oxidative stress, inflammation, and activation of the renin-angiotensin system can induce cardiac remodeling with increased cardiac myocyte and connective tissue matrix accumulation. [33][34][35] The causality of the observed association between childhood adiposity and adulthood LVM cannot be established by this observational study. Persistence of adiposity over time plays a role in this regard.…”
Section: Discussionmentioning
confidence: 77%
“…It has been suggested that increased ROS concentrations may lead to apoptosis during embryo culturing [9]. Among different ROS, H 2 O 2 at high concentrations induces apoptosis [26]. Therefore, this study was conducted to monitor the levels of H 2 O 2 within oocytes to indirectly assess ROS toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrosylation is a physiologically important post-translational modification that affects a wide variety of proteins involved in a number of cellular processes. The term of nitrosative stress implied the hazardous levels of nitrosylation, a situation analogous to and taking place in the presence of oxidative stress which have been implicated in cardiac apoptosis, muscle dysfunction and cell injury [18][19][20]. NO also acts through soluble guanylyl cyclase and activates this enzyme to raise cyclic GMP levels.…”
Section: Discussionmentioning
confidence: 99%